Proposal of Sandwich Composite from Bioresource and Polystyrene Waste Materials - M. ALmusawi, Aqil; Lachat, Remy; Chamoret, Dominique; Atcholi, Kokou; soulama, Sagnaba (International Journal of Engineering and Technology, 2018)
Lately there is a renewed interest in the use of bio-resource materials for the production of ecological, sustainable and inexpensive building materials. Sandwich composite of minimum plastic matrix was manufactured, this was achieved by using the Thermoforming process in two steps. In the first step, the core layer was made when thermo pressed 100% hemp Shive particles under a high pressure. The second step was accomplished by wrapping the core layer with two thermoplastic composite layers of 60% of hemp tissue and 40% recycled Polystyrene. Interestingly, through the first step, elevated temperature treated the core surface (hydrophilic) and gave it greater adherence to the Polystyrene matrix (hydrophobic). Mechanical properties of this proposed sandwich composite of 80 % bio-resource were approximately four times of the Polystyrene resistance. Furthermore, the microscopic study was performed to investigate the bonding of the different components, especially for the binderless core layer. Each individual layer and the sandwich form were mechanically investigated, and the finite element method, via ANSYS, was used to illustrate the stresses in the sandwich structure.Â Â Â